Wear behavior of a multiphase ductile iron produced by quenching and partitioning process. (May 2021) - Dong, Kewen; Lu, Congying; Zhou, Wentao; Northwood, Derek O.; Liu, Cheng
Highlights: Wear behavior of a multiphase ductile iron designed by Q&PBM is investigated. Q&PBM is a process of quenching and partitioning below Ms developed by us. Bainitic ferrite (BF) and film retained austenite (RA) deform readily under wear. Prior martensite (PM) remains unchanged but deflects with (BF + RA)nano deforming. A complex strengthening and toughening effect of multiphase is found during wear. Abstract: A quenching and partitioning process has been developed for an unalloyed ductile iron. The process includes austenitizing at 890 °C for 0.5 h, quenching to 180 °C below the Ms (the starting temperature of martensite transformation) for 5 s, with a controlled speed, then followed by a partitioning at 190 °C (10 °C lower than the Ms) for 8 h, and finally air cooling to the room temperature. A multiphase microstructure consisting of prior martensite (PM), bainitic ferrite (BF), and fresh martensite formed on final quenching (FM) with retained austenite (RA) is obtained through the microstructural evolution on quenching and partitioning steps. Further observation shows that a unique nano structure including lath BF and film RA with a width less than 100 nm nucleates around the PM. A strong influence of RA content and stability on both the tensile strength and the elongation is observed. In addition, the wear behavior is investigated under various loads without lubrication. A combined wear mechanism of abrasion and oxidation is found in a case of a low load. With increasing the load, the wear behavior correlates to a comprehensive strengthening and toughening effect of the multiphase microstructure in the matrix.